FENOMENA KHUTBAH JUM’AT DI KOTA MANADO - Kustini Kustini (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2012)
Friday sermons/Khutbah(s) (speeches) have been one of the methods of religious proselytizing in the Muslim community that is always conducted in various places. The writing is the result of research on the Friday sermons in Manado City as an area that is not predominantly Muslims. The research was conducted with a qualitative approach, and data collection techniques through interviews, document review, and observation. The results show that although the Friday sermon is a consistent proselytizing routine, the mosques which hold Friday prayers have hardly prepared the delivery of the themes. The themes of the speeches are more normative, and a few were based upon Islamic economic activity, harmony, and the establishment of tolerance. One potential implementation is a Friday sermon preacher characteristics that most have an undergrad educational background (S1), and some have post graduate degrees. Various problems faced by preachers are such as minimum financial rewards, the rare training program for the preachers, and the target coverage area is extensive with limited transportation.